Accountability Model of Financial Management in the Public Sector: A Study on Panggungharjo Village Budget - Basuki, Ayudya Fitri; Setyowati, Kristina; Wahyunengseh, Rutiana Dwi (UI Scholars Hub, 2019)
Most research on public accountability is carried out in government agencies. Little looks at the accountability model for village financial management. Little is also known about villages in developing countries having successfully managed their finance that fulfills both formal and substantive aspects of public accountability. This research attempts to analyze Bovens accountability model framework which increases three important accountability elements: right of authority, answerability and enforceability in village financial management. Data are collected through interviews with informants and secondary data from village financial reports. We find that village community forum takes place democratically to ask for accountability but cannot be a substantive accountee. Panggungharjo Village is studied here as depiction of a top performing village at national level that has procedurally and normatively fulfilled the answerability aspect of vertical accountability. However, the potential problem of accountability arises from the essence of accountability from the aspect of democracy, where public participation as accountees is still biased so answerability has not yet emerged on horizontal accountability. Culture of the society and technocratic policies become confounding variables. A theoretical implication simultaneously enriches Bovens’ model is the need to look at the environmental context, namely, bureaucrats’ attitudes in the political context as accountor and the cultural environment of the community as accountee.